Foam scrubbing agent for gathering and transportation pipeline of sulfur-containing gas field
By using a specific ratio of α-alkenyl sulfonate and fatty alcohol polyoxyethylene ether to form an adsorption membrane in the foaming agent, the problems of excessive corrosion and water pollution in the gathering and transportation pipelines of acidic gas fields are solved, achieving a safe and environmentally friendly foaming effect.
Patent Information
- Application Number
- CN202410608549.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-11-18
AI Technical Summary
Existing foaming agents affect the performance of corrosion inhibitors in acidic gas field gathering and transmission pipelines, leading to excessive corrosion and potential water pollution. Therefore, they cannot be safely and effectively used in sulfur-containing gas field gathering and transmission pipelines.
A foaming agent composed of α-olefin sulfonate and fatty alcohol polyoxyethylene ether is used. By controlling the ratio of m+n and x, y in its structural formula, a strong adsorption film is formed to replace the corrosion inhibitor film, thereby reducing corrosion and lowering the risk of water pollution.
It effectively controls pipeline corrosion rates below national standards, reduces the ability of the foaming agent to wash away corrosion inhibitor films, and its components are harmless to water, meeting environmental protection requirements. The materials are widely available and inexpensive.
Smart Images

Figure CN120966447A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of well treatment composition, and particularly relates to a foaming agent for sulfur-containing gas field gathering pipeline. BACKGROUND
[0002] During the process of depletion development, the invasion of edge and bottom water into the gas production area will cause water production in gas wells as the formation pressure gradually decreases. In the gas field using wet gas transportation process, there is no gas-liquid separation at the wellhead and no process for removing free water in the gas phase, so the liquid phase is prone to accumulate in the concave part of the undulating pipeline. The liquid accumulation in the pipeline not only affects the safety of production, but also reduces the stability and gas transportation efficiency of the system, so economic and effective liquid drainage operation is needed. At present, there are mainly two methods for removing liquid accumulation in the gathering pipeline of the gas field: one is mechanical method, using pig to clean the pipeline regularly; the other is chemical method, adding foaming agent in the pipeline to drain the liquid by using the generated foam. For the gathering pipeline with long liquid accumulation period, mechanical pigging can meet the liquid drainage demand; for the gathering pipeline with serious liquid accumulation, frequent pigging not only affects the production, but also increases the risk of sulfur-related operation, especially in the sour gas field. Compared with mechanical pigging, foam drainage only needs to set an injection point at the front end of the liquid accumulation section, and continuously inject foaming agent to remove the liquid in the pipeline in real time, improve the gathering efficiency, and has the characteristics of convenience and low cost.
[0003] The application of existing foaming agents in the gathering and transmission pipelines of acidic gas fields presents two main problems: First, it affects the control of pipeline corrosion. To control the corrosion of gathering and transmission pipelines by acidic gas, continuous injection of corrosion inhibitors is necessary. The mechanism of corrosion inhibitors is to adsorb and form an oil-like "protective film" on the metal pipe wall. This "protective film" effectively prevents acidic gases and liquids from directly contacting the pipe wall, thus avoiding pipeline corrosion. However, foaming agents, composed of foaming surfactants, have a strong ability to reduce interfacial tension. This can cause part of the "protective film" formed by the corrosion inhibitor to be washed away, leaving the pipe wall in direct contact with H2S, leading to pipe wall corrosion and posing a significant safety hazard. The results of the quartz crystal microbalance test on the "protective film quality" before and after the addition of foaming agents showed that nonionic foaming agents (alkyl glycosides APG, alcohol ether glycosides AEG, etc.) can wash away more than 80% of the "protective film", anionic foaming agents (sodium dodecyl sulfate K12, sodium fatty alcohol polyoxyethylene ether sulfate AES, linear alkylbenzene sulfonate sodium LAS, α-alkenyl sulfonate AOS, etc.) can wash away more than 45% of the "protective film", cationic foaming agents (cocamidopropylamine oxide LAO, dodecyl dimethylamine oxide OB-2, etc.) can wash away more than 70% of the "protective film", and amphoteric foaming agents (betaines) can wash away more than 65% of the "protective film". The corrosion test results from the autoclave showed that, under simulated acid gas gathering and transmission pipeline conditions (gas composition, pressure, temperature, corrosion inhibitor, pipeline material), the addition of foaming surfactants such as APG, AES, and AOS caused the corrosion rate of the coated plates to increase from 0.0105 mm / a to 0.7132 mm / a (APG), 0.2541 mm / a (AES), and 0.1119 mm / a (AOS) due to the removal of most of the "protective film," significantly exceeding the national standard of 0.076 mm / a. Secondly, it pollutes water bodies. After the gas field's gathering and transmission pipelines encounter water, the large accumulation of liquid leads to a high dosage of foaming agents. If the foaming agent contains nitrogen and phosphorus, it can cause the death of activated sludge in downstream water treatment processes, paralyzing the water treatment system and causing eutrophication of water discharged into the environment, harming aquatic life and causing water pollution.
[0004] Chinese patent application CN104140802A, published on November 12, 2014, discloses a foaming agent for gas well drainage and gas production. This foaming agent is composed of a mixture of gemini surfactant, amphoteric surfactant, high-bond-energy surfactant, and polymer, and is applied to wellbore drainage in gas fields with high H2S content. The gemini surfactant is a quaternary ammonium salt, the amphoteric surfactant is alkanolamide betaine, the high-bond-energy surfactant is a N-containing fluorocarbon surfactant, and the polymer is polyacrylamide. All of the above components contain nitrogen, which enriches the water body with oxygen, and the interaction with corrosion inhibitors is not considered. Quartz crystal microbalance test shows that it reduces the quality of the "protective film" by 82%.
[0005] Chinese Patent Application No. CN114774095A, published on July 22, 2022, discloses a foaming agent composition and its preparation method and application. The foaming agent composition consists of 1 part foaming agent, 0.01-10 parts foam stabilizer, and the balance water. The foaming agent is a betaine surfactant, and the foam stabilizer is rice husk-derived carbon particles. This foaming agent is applied to the drainage of acidic gas field wells without considering its interaction with corrosion inhibitors. Quartz crystal microbalance tests show that it reduces the quality of the "protective film" by 79% and contains nitrogen element that enriches the water body with oxidation.
[0006] In June 2023, Dong Jie disclosed three compound foaming agent formulations 4D-1 / 2 / 3 in her article "Research on Integrated Foaming-Hydrate Anti-polymerization-Corrosion Inhibitor". Among them, the 4D-1 formulation is: 0.05% hexadecyltrimethylammonium chloride (CTAC) + 0.7% cocamidopropyl betaine (CDAB) + 0.6% fatty alcohol polyoxyethylene ether (AEO7) + 0.05% sodium α-alkenyl sulfonate (AOST), which has good foaming performance and corrosion inhibition performance.
[0007] However, the main drawbacks of the above formula are: First, it still causes excessive pipeline corrosion when used in acidic gas fields. Quartz microbalance tests show that it reduces the quality of the "protective film" by 75%. Even with the addition of corrosion inhibitors, the corrosion rate still reaches 0.2211 mm / a, far exceeding the national standard requirements. Therefore, the existing foaming agents still have the problem of affecting the performance of corrosion inhibitors, leading to excessive corrosion in gathering and transmission pipelines of sulfur-containing gas fields. Second, both hexadecyltrimethylammonium chloride (CTAC) and cocamidopropyl betaine (CDAB) in the formula contain nitrogen (N) which pollutes water bodies and cannot be used on a large scale in gathering and transmission pipelines. Summary of the Invention
[0008] The purpose of this invention is to provide a foaming agent for sulfur-containing gas field gathering and transmission pipelines, solving the problem that existing foaming agents affect the performance of corrosion inhibitors, leading to excessive corrosion in sulfur-containing gas field gathering and transmission pipelines.
[0009] To solve the above-mentioned technical problems, the technical solution of the foaming agent for sulfur-containing gas field gathering and transmission pipelines of the present invention is as follows:
[0010] A foaming agent for gathering and transmission pipelines in sulfur-containing gas fields, wherein the foaming agent is composed of 15-25% by mass of α-alkenyl sulfonate, fatty alcohol polyoxyethylene ether, and the balance water, wherein the fatty alcohol polyoxyethylene ether has a mass fraction of not less than 8%, and the structural formula of the α-alkenyl sulfonate is shown in Formula I:
[0011]
[0012] Where n is 1 to 3, the sum of m and n is 12 to 18, and M + They are alkali metal ions;
[0013] The structural formula of the fatty alcohol polyoxyethylene ether is shown in Formula II:
[0014] C x H 2x+1 -O-(CH2CH2O) y -H Formula II;
[0015] Among them, C x H 2x+1 For straight-chain alkanes, when x is 16–18, y is 15–25.
[0016] This invention improves upon existing technology, providing a foaming agent for sulfur-containing gas field gathering and transmission pipelines. α-Alkenyl sulfonate, acting as a foaming agent, can form foam with natural gas and water, carrying away accumulated liquid. However, this type of foaming agent has a relatively weak ability to wash away the "adsorption film"—quartz microbalance testing shows it washes away 46% of the "protective film." By controlling the m+n = 12-18 in the α-alkenyl sulfonate structural formula, the foaming performance and water solubility of the foaming agent can be controlled. The invention utilizes the oxygen atom of the hydrophilic ether bond (-O-) in fatty alcohol polyoxyethylene ether to form a coordination bond with iron atoms on the gathering and transmission pipeline surface. The hydrophobic alkane group forms an adsorption film on the pipeline surface, filling the positions of the corrosion inhibitor washed away by the foaming agent α-alkenyl sulfonate, ensuring no corrosion and promptly repairing the "protective film." This product helps improve the hard water resistance of α-alkenyl sulfonate. By controlling the x component in the fatty alcohol polyoxyethylene ether structural formula, the thickness and solubility of the adsorption film formed by the hydrophobic group are controlled. By controlling the y component in the fatty alcohol polyoxyethylene ether structural formula, the interaction between the hydrophilic group and the iron surface of the pipeline is controlled, and the washing ability of the fatty alcohol polyoxyethylene ether on the corrosion inhibitor film is also controlled. When the mass percentage is less than 15%, the liquid carrying capacity does not meet the relevant standard requirements due to the low concentration. When the mass percentage is greater than 25%, the concentration increases, the amount of "protective film" washed away increases, and the corrosion exceeds the standard. By compounding α-alkenyl sulfonate and fatty alcohol polyoxyethylene ether in a certain ratio, the washing ability of the foaming agent on the corrosion inhibitor film can be alleviated, thereby ensuring that the pipeline corrosion does not exceed the standard after adding the foaming agent under the original production conditions.
[0017] After the addition of the foaming agent of this invention, the anionic surfactant (α-alkenyl sulfonate) washes away part of the corrosion inhibitor "oil film," while the nonionic surfactant (fatty alcohol polyoxyethylene ether) forms strong coordination bonds with the lone pairs of oxygen atoms in the numerous ether bonds (-O-) of the nonionic surfactant and the empty channels of iron atoms in the gathering and transportation pipeline. This instantly occupies the position of the washed-away corrosion inhibitor and acts as a substitute for the corrosion inhibitor. The foaming agent of this invention makes the corrosion rate of the gathering and transportation pipeline much lower than the national standard requirement (0.076 mm / a), greatly alleviating the problem of excessive corrosion in the gathering and transportation pipeline of sulfur-containing gas fields due to the influence of the foaming agent on the performance of the corrosion inhibitor. Moreover, the components of the foaming agent are all straight-chain alkanes with excellent biodegradability, and do not contain N and P elements that are harmful to water bodies, which meets the requirements of environmental protection. The raw materials are widely available and inexpensive, and can be used in large quantities for a long time.
[0018] To further improve the corrosion resistance rate of the foaming agent by replacing corrosion inhibitors, while reducing the amount of fatty alcohol polyoxyethylene ether used and thus lowering the cost of the foaming agent, preferably, the mass fraction of the fatty alcohol polyoxyethylene ether is 8-16%. Using less fatty alcohol polyoxyethylene ether also reduces the viscosity of the system, which is beneficial for field use.
[0019] To further reduce the impact of the foaming agent on downstream water treatment processes, preferably, the alkali metal ion is sodium ion or potassium ion.
[0020] To further improve the liquid-carrying capacity of the foaming agent, reduce the washing effect on the oil film formed by the corrosion inhibitor, and slow down the pipeline corrosion rate, the foaming agent is preferably composed of 18-20% α-olefin sulfonate, 10-12% fatty alcohol polyoxyethylene ether, and the balance water.
[0021] To further control the interaction of the various groups in the components, preferably, in Formula I, n is 1 to 3, and the sum of m and n is 12 to 14; in Formula II, x is 16 and y is 15.
[0022] To further control the interaction of the various groups in the components and mitigate the corrosive effect of the foaming agent on the pipeline, preferably, in Formula I, n is 1 to 3, and the sum of m and n is 14 to 16, and in Formula II, x is 18 and y is 25.
[0023] To further control the interaction of the various groups in the components, reduce the influence of the foaming agent on the adsorption film of the corrosion inhibitor, and slow down the corrosion performance, preferably, in Formula I, n is 1 to 3, and the sum of m and n is 16 to 18; in Formula II, x is 16 to 18, and y is 20. Attached Figure Description
[0024] Figure 1 This is a schematic diagram illustrating the interaction mechanism between foaming agents and corrosion inhibitors in existing technologies.
[0025] Figure 2 This is a schematic diagram illustrating the interaction mechanism between the foaming agent and the corrosion inhibitor provided by the present invention. Detailed Implementation
[0026] The technical concept of the foaming agent for sulfur-containing gas field gathering and transmission pipelines provided by this invention is as follows:
[0027] A foaming agent for gathering and transmission pipelines in sulfur-containing gas fields, wherein the foaming agent is composed of 15-25% by mass of α-alkenyl sulfonate, fatty alcohol polyoxyethylene ether, and the balance water, wherein the fatty alcohol polyoxyethylene ether has a mass fraction of not less than 8%, and the structural formula of the α-alkenyl sulfonate is shown in Formula I:
[0028]
[0029] Where n is 1 to 3, the sum of m and n is 12 to 18, and M + They are alkali metal ions;
[0030] The structural formula of the fatty alcohol polyoxyethylene ether is shown in Formula II:
[0031] C x H 2x+1 -O-(CH2CH2O) y -H Formula II;
[0032] Among them, C x H 2x+1 For straight-chain alkanes, when x is 16–18, y is 15–25.
[0033] The foaming agents used in existing technologies are composed of surfactants with foaming properties. These agents have a strong ability to reduce interfacial tension, which can wash away part of the "protective film" formed by the corrosion inhibitor. The washed-off area then comes into direct contact with H2S, leading to pipe wall corrosion and posing a significant safety hazard. The mechanism of action between the foaming agents and corrosion inhibitors in existing technologies is as follows: Figure 1As shown, the results of the quartz crystal microbalance test on the "protective film quality" before and after adding foaming agents show that nonionic foaming agents (alkyl glycosides APG, alcohol ether glycosides AEG, etc.) can wash away more than 80% of the "protective film", anionic foaming agents (sodium dodecyl sulfate K12, sodium fatty alcohol polyoxyethylene ether sulfate AES, linear alkylbenzene sulfonate sodium LAS, α-alkenyl sulfonate AOS, etc.) can wash away more than 45% of the "protective film", cationic foaming agents (cocamidopropylamine oxide LAO, dodecyl dimethylamine oxide OB-2, etc.) can wash away more than 70% of the "protective film", and amphoteric foaming agents (betaines) can wash away more than 65% of the "protective film". The corrosion test results from the autoclave showed that, under simulated acid gas gathering and transmission pipeline conditions (gas composition, pressure, temperature, corrosion inhibitor, pipeline material), the addition of foaming surfactants such as APG, AES, and AOS caused the corrosion rate of the coated plates to increase from 0.0105 mm / a to 0.7132 mm / a (APG), 0.2541 mm / a (AES), and 0.1119 mm / a (AOS) due to the removal of most of the "protective film," significantly exceeding the national standard of 0.076 mm / a. Secondly, it pollutes water bodies. After the gas field's gathering and transmission pipelines encounter water, the large accumulation of liquid leads to a high dosage of foaming agents. If the foaming agent contains nitrogen and phosphorus, it can cause the death of activated sludge in downstream water treatment processes, paralyzing the water treatment system and causing eutrophication of water discharged into the environment, harming aquatic life and causing water pollution.
[0034] The α-alkenyl sulfonate in the foaming agent for sulfur-containing gas field gathering and transmission pipelines provided by this invention acts as a foamer, forming foam with natural gas and accumulated liquid in the pipeline, carrying away the accumulated liquid. This type of foaming agent has a relatively weak ability to wash away the "adsorption film"; quartz microbalance testing shows that it washes away 46% of the "protective film." When the sum of m and n is greater than 18, the water solubility deteriorates, and a homogeneous solution cannot be formed; when the sum of m and n is less than 12, the foaming performance is poor, failing to meet the liquid carrying capacity required by relevant standards; when the mass percentage is less than 15%, the liquid carrying capacity does not meet the relevant standards due to the low concentration; when the mass percentage is greater than 25%, the concentration increases, the amount of "protective film" washed away increases, and corrosion exceeds the standard. By compounding α-alkenyl sulfonate and fatty alcohol polyoxyethylene ether in a certain ratio, the foaming agent's ability to wash away the corrosion inhibitor film can be mitigated, thereby ensuring that pipeline corrosion does not exceed the standard after adding the foaming agent under the original production conditions.
[0035] Meanwhile, the main function of fatty alcohol polyoxyethylene ether is to promptly repair the "protective film," ensuring its integrity and effectively controlling corrosion. The primary mechanism involves the formation of coordination bonds between the oxygen atom of the hydrophilic ether bond (-O-) and the iron atoms exposed on the pipeline surface after the "protective film" is washed away by the foaming surfactant α-alkenyl sulfonate. This allows for relatively strong adsorption onto the pipeline wall surface. The hydrophobic alkane group forms an adsorption film on the pipeline surface, filling the spaces left by the foaming agent α-alkenyl sulfonate to prevent corrosion and further enhancing the corrosion resistance of the α-alkenyl sulfonate. The hard water resistance of alkenyl sulfonate is controlled by adjusting x in the fatty alcohol polyoxyethylene ether structural formula to control the thickness and solubility of the adsorption film formed by the hydrophobic group, and by adjusting y in the fatty alcohol polyoxyethylene ether structural formula to control the interaction between the hydrophilic group and the iron surface of the pipeline, as well as the washing ability of the fatty alcohol polyoxyethylene ether on the corrosion inhibitor film. When x is less than 16, the hydrophobic group is too short, and the thickness of the adsorption film formed does not meet the requirements for protecting the pipe wall, resulting in excessive corrosion. When x is greater than 18, the hydrophobic group is too long, the solubility in water decreases, and a solution cannot be formed. When y is less than 15, there are too few adsorption sites, and the probability of interaction with iron atoms is too small, so the "protective film" washed away by the foaming agent cannot be repaired in time. In addition, the water solubility becomes poor and it cannot form a solution. When y is greater than 25, the hydrophilicity is too strong, which aggravates the ability to wash the "protective film" of the corrosion inhibitor, resulting in excessive corrosion and failing to achieve the intended effect. However, by compounding α-alkenyl sulfonate and fatty alcohol polyoxyethylene ether in a certain ratio, the ability of the foaming agent to wash the corrosion inhibitor film can be alleviated, thereby reducing pipeline corrosion problems.
[0036] The functions of the foaming agent and corrosion inhibitor provided by this invention are as follows: Figure 2 As shown, after the addition of the foaming agent, the anionic surfactant (α-alkenyl sulfonate) washes away part of the corrosion inhibitor "oil film," while the nonionic surfactant (fatty alcohol polyoxyethylene ether) forms strong coordination bonds with the lone pairs of oxygen atoms in its numerous ether bonds (-O-) and the empty channels of iron atoms in the gathering and transportation pipeline. This instantly occupies the positions of the washed-away corrosion inhibitor, acting as a substitute for the corrosion inhibitor. The foaming agent of this invention makes the corrosion rate of the gathering and transportation pipeline far lower than the national standard requirement (0.076 mm / a), greatly alleviating the problem of excessive corrosion in the gathering and transportation pipelines of sulfur-containing gas fields due to the influence of the foaming agent on the performance of the corrosion inhibitor. Moreover, the components of the foaming agent are all straight-chain alkanes with excellent biodegradability, and do not contain N and P elements that are harmful to water bodies, meeting environmental protection requirements. The raw materials are widely available and inexpensive, and can be used in large quantities for a long time.
[0037] In a specific embodiment, in Formula II, x = 16 to 18 and y = 15 to 25. The fatty alcohol polyoxyethylene ether can be x and y independently taken from an integer, or it can be a mixture of multiple structures formed by x and y taking different integers.
[0038] In a specific embodiment, the preparation method of the foaming agent is as follows: the α-alkenyl sulfonate and the fatty alcohol polyoxyethylene ether are added to water at 50-60°C and stirred until dissolved; specifically, the fatty alcohol polyoxyethylene ether is first added to water at 50-60°C and stirred until dissolved, and then the α-alkenyl sulfonate is added and stirred until dissolved.
[0039] The embodiments of the present invention will be further described below with reference to specific examples, but the content of the present invention is not limited to the following examples. Unless otherwise specified, the chemical reagents involved in the following examples are all commercially available conventional products.
[0040] I. Specific Embodiments of the Foaming Agent for Sulfur-Containing Gas Field Gathering and Transmission Pipelines of the Present Invention
[0041] Example 1
[0042] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this embodiment is prepared by the following method:
[0043] Add 59% water to a stirrer-equipped and heated reactor. Turn on the stirrer and heating device, raise the temperature to 55±5℃ and maintain a constant temperature. Then, while stirring, add 16% of the nonionic surfactant fatty alcohol polyoxyethylene ether (x = 16, y = 15, purchased from Jiangsu Haian Petrochemical Plant, model: cetyl alcohol polyoxyethylene ether Pingpingjia O-15). After it is completely dissolved, add 25% of the anionic surfactant α-olefin sulfonate sodium (n = 1-3, the sum of m and n is 12-14, Beijing Huamei Huli Biochemical, C12-C14 olefin sulfonate sodium), and stir until it is uniformly dissolved.
[0044] Example 2
[0045] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this embodiment is prepared by the following method:
[0046] Add 68% water to a stirrer-equipped and heated reactor. Turn on the stirrer and heating device, raise the temperature to 55±5℃ and maintain a constant temperature. Then, while stirring, add 12% of the nonionic surfactant fatty alcohol polyoxyethylene ether (x = 18, y = 25, purchased from Jiangsu Haian Petrochemical Plant, model: stearyl alcohol polyoxyethylene ether Pingpingjia O-25). After it is completely dissolved, add 20% of the anionic surfactant α-alkenyl sulfonate sodium (n = 1-3, the sum of m and n is 14-16, Yuantailun Chemical, C14-C16 alkenyl sulfonate sodium), and stir until it is uniformly dissolved.
[0047] Example 3
[0048] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this embodiment is prepared by the following method:
[0049] Add 77% water to a stirrer-equipped and heated reactor. Turn on the stirrer and heating device, raise the temperature to 55±5℃ and maintain a constant temperature. Then, while stirring, add 8% of the nonionic surfactant fatty alcohol polyoxyethylene ether (x = 16-18, y = 20, purchased from Jiangsu Haian Petrochemical Plant, model: cetearyl alcohol polyether Pingpingjia O-20). After it is completely dissolved, add 15% of the anionic surfactant sodium α-alkenyl sulfonate (n = 1-3, the sum of m and n = 16-18, Ao Ke New Material Technology (Shanghai) Co., Ltd., C16-C18 sodium α-alkenyl sulfonate). Stir until it is evenly dissolved.
[0050] Example 4
[0051] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this embodiment is prepared by the following method:
[0052] Add 68% water to a stirrer-equipped and heated reactor. Turn on the stirrer and heating device, raise the temperature to 55±5℃ and maintain a constant temperature. Then, while stirring, add 12% of the nonionic surfactant fatty alcohol polyoxyethylene ether (x = 18, y = 25, purchased from Jiangsu Haian Petrochemical Plant, model: stearyl alcohol polyoxyethylene ether Pingpingjia O-25). After it is completely dissolved, add 20% of the anionic surfactant α-alkenyl sulfonate potassium (n = 1-3, the sum of m and n is 14-16, Yuantailun Chemical, C14-16 alkenyl sulfonate sodium), and stir until it is uniformly dissolved.
[0053] Example 5
[0054] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this embodiment is prepared by the following method:
[0055] Add 63% water to a stirrer-equipped and heated reactor. Turn on the stirrer and heating device, raise the temperature to 55±5℃ and maintain a constant temperature. Then, while stirring, add 17% of the nonionic surfactant fatty alcohol polyoxyethylene ether (x = 18, y = 25, purchased from Jiangsu Haian Petrochemical Plant, model: stearyl alcohol polyoxyethylene ether Pingpingjia O-25). After it is completely dissolved, add 20% of the anionic surfactant α-alkenyl sulfonate potassium (n = 1-3, the sum of m and n is 14-16, Yuantailun Chemical, C14-16 alkenyl sulfonate sodium), and stir until it is uniformly dissolved.
[0056] II. Comparative Example
[0057] The foaming and drainage agents for sulfur-containing gas field gathering and transmission pipelines in Comparative Examples 1–9 were prepared by the following method:
[0058] Water was added to a stirrer-equipped and heated reactor. The stirrer and heating device were turned on, and the temperature was raised to 55±5℃ and maintained at a constant temperature. Then, the nonionic surfactant fatty alcohol polyoxyethylene ether was added and completely dissolved while stirring. Next, the anionic surfactant α-alkenyl sulfonate was added, and the mixture was stirred until homogeneous. The molecular structures and mass percentages of water, fatty alcohol polyoxyethylene ether, and α-alkenyl sulfonate are shown in Table 1.
[0059] Table 1 Formulations for Comparative Examples 1–9
[0060]
[0061]
[0062] Comparative Example 10
[0063] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this comparative example was prepared by the following method:
[0064] Add 15% by mass of quaternary ammonium salt gemini surfactant 12-3-12, 20% by mass of cocoylamine propyl betaine, 2% by mass of fluorocarbon surfactant FS-73, and 5% by mass of polyacrylamide (molecular weight 6×10⁻⁶) to a reactor equipped with a stirrer. 9 Mix g / mol of water with 58% by mass and stir for 30 minutes until completely dissolved to obtain a high-temperature, high-salinity foaming agent resistant to a wide pH range for drainage and gas extraction.
[0065] Comparative Example 11
[0066] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this comparative example was prepared by the following method:
[0067] Under normal temperature and pressure conditions, weigh carboxybetaine (x=11, n=6), prepare a 0.5% carboxybetaine solution, add rice husk-derived carbon particles at a mass ratio of 50:1 (carboxybetaine to rice husk-derived carbon particles), mix well, and the foaming agent composition can be obtained. The method for preparing rice husk-derived carbon particles in this embodiment is as follows: Naturally air-dried rice husks are placed in a tube furnace and heated to 700°C under N2 protection (heating rate 10°C / min). The calcination is then carried out at 700°C for 2 hours, followed by natural cooling to obtain rice husk biochar. The rice husk biochar is then placed in a ball mill (containing 14 small steel balls with a diameter of 6.35 mm and 8 large steel balls with a diameter of 9.5 mm) and uniformly pulverized at 300 Hz for 30 minutes to obtain rice husk-derived carbon powder with a particle size of 30 μm. The rice husk-derived carbon powder is then immersed in a 0.1 mol / L trimethylchlorosilane ethanol solution for 2 hours, followed by vacuum drying at 80°C for 4 hours to obtain rice husk-derived carbon particles.
[0068] Comparative Example 12
[0069] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this comparative example was prepared by the following method:
[0070] Cetyltrimethylammonium chloride (CTAC), cocamidopropyl betaine (CDAB), fatty alcohol polyoxyethylene ether (AEO7), and sodium α-alkenyl sulfonate (AOST) were added to distilled water to make their mass concentrations 0.05%, 0.7%, 0.6%, and 0.05%, respectively.
[0071] Comparative Example 13
[0072] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this comparative example was prepared by the following method:
[0073] Fatty alcohol polyoxyethylene ether (AEO-7) and sodium α-olefin sulfonate (AOST) were added to distilled water to achieve mass concentrations of 0.6% and 0.05%, respectively.
[0074] Comparative Example 14
[0075] The foaming agent for sulfur-containing gas field gathering and transmission pipelines in this comparative example was prepared by the following method:
[0076] Fatty alcohol polyoxyethylene ether (AEO-7) and sodium α-olefin sulfonate (AOST) were added to distilled water to make their mass concentrations 16% and 15%, respectively.
[0077] III. Experimental Examples
[0078] Experimental Example 1
[0079] This experimental example was tested in accordance with the standard Q / SH CG0135—2021 "Technical Requirements for Foaming Agents". The standard requires a liquid carrying capacity of ≥120mL. The test results are shown in Table 2.
[0080] Table 2. Liquid carrying capacity test results of the foaming agents in Examples 1-5 and Comparative Examples 1-14
[0081] Carried liquid amount / mL Note Example 1 150 Example 2 180 Example 3 140 Example 4 168 Example 5 180 Comparative Example 1 80 Comparative Example 2 50 Layering occurred Comparative Example 3 190 Comparative Example 4 162 Layering occurred Comparative Example 5 156 Layering occurred Comparative Example 6 185 Comparative Example 7 110 Comparative Example 8 185 Comparative Example 9 180 Comparative Example 10 180 Comparative Example 11 160 Comparative Example 12 180 Comparative Example 13 30 Comparative Example 14 150
[0082] Test results show that when the hydrophobic chain of the anionic surfactant α-alkenyl sulfonate sodium is too short (m+n < 12), its foaming performance is poor and its liquid carrying capacity is substandard. Conversely, when the hydrophobic chain is too long (m+n > 18), its water solubility is poor, resulting in stratification and failure to form a solution, thus also failing to meet the liquid carrying capacity standard (see Comparative Examples 1 and 2). When its mass percentage is < 15%, its foaming performance is poor and its liquid carrying capacity is substandard due to the low concentration (see Comparative Example 7). When the hydrophobic chain of the nonionic surfactant fatty alcohol polyoxyethylene ether is too long or its hydrophilic chain is too short, its water solubility deteriorates, and it cannot form a solution (see Comparative Examples 4 and 5). Comparative Example 13, due to its low content of foaming components, has a liquid carrying capacity far below the standard requirements and cannot be used as a foaming agent.
[0083] Experimental Example 2
[0084] The effect of foaming agents on the "protective film" formed by corrosion inhibitors was investigated using a quartz crystal microbalance. The main test focused on the quality of the "protective film" before and after the addition of the foaming agent. The test water consisted of sodium chloride and calcium chloride with a mineralization of 10 × 10⁻⁶. 4 mg / L simulated water, simulating Ca in water 2+ The concentration was 2500 mg / L. The test method involved measuring the mass change of the chip in a quartz crystal microbalance under fluid flow conditions. Given the known chip area, the adsorbed mass per unit area of the chip was calculated in real time, i.e., the adsorption amount.
[0085] The testing steps are as follows:
[0086] Step 1: Use stainless steel chips, clean them with ethanol, dry them with nitrogen, and set them aside for use.
[0087] Step 2: Create a simulated water baseline. Since the test temperature is 50 degrees Celsius, the simulated water is preheated to 50 degrees Celsius and kept at that temperature. The flow state test simulates the change in water frequency.
[0088] Step 3: After the test value stabilizes, switch to 0.2% corrosion inhibitor (the corrosion inhibitor model is CI1204, manufactured by WESTHAVEN CHEMICAL TECHNOLOGIES CANADA LIMITED, USA);
[0089] Step 4: After the corrosion inhibitor CI1204 is saturated with adsorption, switch to a mixed sample of foaming agent and corrosion inhibitor to simulate the continuous addition of corrosion inhibitor and foaming agent on site. The mass concentration of corrosion inhibitor in the mixed sample is 0.2% and the mass concentration of foaming agent is 0.2%. Test the sample and conduct the next experiment after the values have stabilized for 5 minutes.
[0090] Step 5: Clean the chip and move on to the next experiment. The test results for the foaming agents used in the examples, comparative examples, and prior art are shown in Table 3.
[0091] Table 3. Test results on the effect of adding foaming agent on the "adsorption film quality" of corrosion inhibitor.
[0092]
[0093]
[0094] Test results show that: commonly used nonionic foaming agents such as APG and AEG reduce the quality of the "protective film" by more than 80%; anionic foaming agents such as K12, AES, and LAS reduce the quality of the "protective film" by more than 60%; cationic foaming agents such as LAO and OB-2 reduce the quality of the "protective film" by more than 70%; and amphoteric foaming agents such as betaine reduce the quality of the "protective film" by more than 65%.
[0095] Comparative Examples 10 and 11, due to the lack of a "protective film" effect and the use of surfactants with strong "protective film" washing capabilities, experienced a decrease in "protective film" quality of 82% and 79%, respectively. AEO-7 tests in Comparative Examples 12, 13, and 14 showed that no effective replacement "protective film" was formed in sulfur-containing environments.
[0096] In this invention, when the hydrophobic chain of the fatty alcohol polyoxyethylene ether is too short (x < 16), the formed "protective film" cannot compensate for the loss of the "protective film" formed by the corrosion inhibitor, resulting in a decrease in the quality of the "protective film" (see Comparative Example 3). When the hydrophilic chain is too long (y > 25), the ability of the foaming agent to wash away the "protective film" is further enhanced, leading to a decrease in the quality of the "protective film" (see Comparative Example 6). When its mass percentage is small, due to the low content, the number of adsorbable molecules is small, which cannot completely compensate for the loss of the "protective film" formed by the corrosion inhibitor washed away by the foaming agent, resulting in a decrease in the quality of the "protective film" (see Comparative Example 9). When the selected fatty alcohol polyoxyethylene ether has poor solubility, stratification occurs. The upper liquid contains a small amount of fatty alcohol polyoxyethylene ether, which is insufficient to completely replace the mass of the "protective film" washed away by the foaming agent, resulting in a decrease in the quality of the "protective film" (see Comparative Examples 4 and 5).
[0097] This experiment also verified that when the alkyl chain of fatty alcohol polyoxyethylene ether is too short, i.e., x < 16, and the number of ethylene oxide units is small, i.e., y < 15, such as AEO-7, it cannot effectively form a substitute "protective film" (see Comparative Example 14), resulting in a 45% decrease in the quality of the "protective film", which is comparable to the ability of AOS alone to wash the "protective film".
[0098] Experimental Example 3
[0099] This experiment tests the corrosion rate of pipelines using a foaming agent in a high-hydrogen sulfide environment. The testing equipment used a high-temperature, high-pressure reactor, and the test water consisted of sodium chloride and calcium chloride with a mineralization of 10 × 10⁻⁶. 4 mg / L simulated water, simulating Ca in water 2+ The concentration is 2500 mg / L. The test method and steps are as follows:
[0100] Step 1: Pre-treatment and placement of the hanging clips
[0101] Pretreatment of the hanging plates: L360QCS steel hanging plates were used (6 hanging plates per experiment, length × width × height = 5.0000 × 1.0000 × 0.3000 cm). According to standard Q / SH1025 0876-2013, the hanging plates were first degreased and descaled, cleaned with petroleum ether and anhydrous ethanol, weighed, and then hung on the liquid phase hanging plate rack in the high temperature and high pressure reactor.
[0102] Step 2: Prepare 1800 mL of corrosion inhibitor CI12O4 solution with a mass concentration of 0.2% and add it to the high-temperature and high-pressure reactor. Then, quickly seal the high-pressure reactor and purge the residual air with nitrogen for 10 min.
[0103] Step 3: Air tightness test: Use high-purity N2 gas to conduct an air tightness test to check for leaks in the seals and pipelines.
[0104] Step 4: Increase temperature and pressure
[0105] According to the experimental operating procedures, the temperature was raised to the experimental temperature of 60℃, and 1.5MPa H2S, 1.0MPa CO2, and finally N2 were added in sequence to 10MPa. At this point, the timing was started.
[0106] Step 5: When the cumulative time reaches 168 hours, the experiment ends. After depressurization and cooling, open the lid of the high-temperature and high-pressure reactor and remove the sample. Place the sample in a plastic cup and wash it carefully with distilled water to remove any residual solution from the sample surface. Then, clean the surface corrosion products with acid pickling solution. Finally, place the sample in a desiccator to dry for 24 hours and weigh it.
[0107] Step 6: Based on the weight before and after and the known density, calculate the corrosion rate of the coupon in the liquid, and derive the average corrosion rate as V0, in mm / a.
[0108] Step 7: Replace the corrosion inhibitor solution from Step 2 with a mixed solution of corrosion inhibitor and foaming agent. The mass concentration of the corrosion inhibitor in the mixed solution is 0.2%, and the mass concentration of the foaming agent is 0.2%. Repeat steps 1 to 6 above. Finally, calculate the corrosion rate after adding the foaming agent, in mm / a. The corrosion rate test results of the high sulfur content gathering and transportation pipeline after adding the foaming agent are shown in Table 4.
[0109] Table 4. Test results of corrosion rate of high sulfur-containing gathering and transportation pipelines after addition of desiccant.
[0110]
[0111] The results of this test further validated Test Example 2: Comparative Examples 1, 2, 12, 13, and 14 showed that the lack of a replacement "protective film" and the ability to wash away the "protective film" formed by the corrosion inhibitor led to a decrease in the quality of the "protective film." The reduced quality of the "protective film" resulted in the exposure of the unadsorbed portions of the gathering and transportation pipeline to the H2S environment, leading to an excessive corrosion rate (the standard requirement is 0.076 mm / a).
[0112] In this invention, when the hydrophobic chain of the fatty alcohol polyoxyethylene ether is too short, it cannot form effective protection, leading to a decrease in the quality of the "protective film." The pipe wall is not completely protected by the adsorbed film, resulting in excessive corrosion (see Comparative Examples 3, 12, 13, and 14). When the hydrophilic chain is too long, the "oil-washing ability" of the foaming agent is enhanced, significantly reducing the quality of the "protective film." A large amount of corrosion inhibitor is washed away, leading to excessive corrosion (see Comparative Example 6). When the mass percentage is low, the number of molecules per unit mass is small, which cannot adequately repair the washed-away "protective film," causing excessive corrosion (see Comparative Example 9). When the selected fatty alcohol polyoxyethylene ether has poor solubility, stratification occurs. The upper liquid contains a small amount of fatty alcohol polyoxyethylene ether, insufficient to completely replace the mass of the "protective film" washed away by the foaming agent. As a result, the parts of the gathering and transportation pipeline without an adsorbed film are exposed to the H2S environment, leading to excessive corrosion rates (standard requirement 0.076 mm / a) (see Comparative Examples 4 and 5).
[0113] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A foaming agent for sulfur-containing gas field gathering and transmission pipelines, characterized in that, The foaming agent is composed of 15-25% by mass of α-alkenyl sulfonate, fatty alcohol polyoxyethylene ether, and the balance water, wherein the fatty alcohol polyoxyethylene ether has a mass fraction of not less than 8%, and the structural formula of the α-alkenyl sulfonate is shown in Formula I: Where n is 1 to 3, the sum of m and n is 12 to 18, and M + They are alkali metal ions; The structural formula of the fatty alcohol polyoxyethylene ether is shown in Formula II: C x H 2x+1 -O-(CH2CH2O) y -H Formula II; Among them, C x H 2x+1 For straight-chain alkanes, when x is 16–18, y is 15–25.
2. The foaming agent for sulfur-containing gas field gathering and transmission pipelines as described in claim 1, characterized in that, The mass fraction of the fatty alcohol polyoxyethylene ether is 8-16%.
3. The foaming agent for sulfur-containing gas field gathering and transmission pipelines as described in claim 1 or 2, characterized in that, The alkali metal ions are sodium ions or potassium ions.
4. The foaming agent for sulfur-containing gas field gathering and transmission pipelines as described in claim 1, characterized in that, The foaming agent consists of 18-20% by mass of α-olefin sulfonate, 10-12% by mass of fatty alcohol polyoxyethylene ether, and the balance being water.
5. The foaming agent for sulfur-containing gas field gathering and transmission pipelines as described in claim 1, characterized in that, In Equation I, n is 1 to 3, and the sum of m and n is 12 to 14. In Equation II, x is 16 and y is 15.
6. The foaming agent for sulfur-containing gas field gathering and transmission pipelines as described in claim 1, characterized in that, In Equation I, n is 1 to 3, and the sum of m and n is 14 to 16. In Equation II, x is 18 and y is 25.
7. The foaming agent for sulfur-containing gas field gathering and transmission pipelines as described in claim 1, characterized in that, In Equation I, n is 1 to 3, and the sum of m and n is 16 to 18. In Equation II, x is 16 to 18, and y is 20.
Citation Information
Patent Citations
Foam drainage agent for gas well drainage gas recovery
CN104140802A
Foam scrubbing agent composition as well as preparation method and application thereof
CN114774095A